Preparation method and application of Ti-doped ultra-stable Y-type molecular sieve catalyst
By introducing titanium atoms into the molecular sieve, regulating acid sites, and preparing Ti-doped super-stable Y-type molecular sieve catalysts, the complex and cost-effective problems of traditional lactic acid production processes are solved, and the efficient and economical production of ethyl lactate is achieved, which simplifies the The process flow and reduce environmental pollution.
Patent Information
- Application Number
- CN202411272406.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-17
AI Technical Summary
The traditional lactic acid production process is complex and costly, and it is necessary to develop a new chemical catalytic process to directly extract lactic acid from raw material biomass, simplify the process flow and reduce production costs.
Ti doped superstable Y-type molecular sieve catalyst is used to introduce titanium atoms into the molecular sieve, regulate the proportion of acidic sites, improve the activity and selectivity of the catalyst, and simplify the reaction process of converting dihydroxyacetone into ethyl lactate.
It significantly improves the catalytic efficiency and the yield of ethyl lactate, simplifies the process flow, reduces the generation of by-products and environmental pollution, and achieves efficient and economical production of ethyl lactate.
Smart Images

Figure CN119318991A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of petroleum processing and petrochemical catalyst application, and specifically relates to a preparation method and application of a Ti-doped ultra-stable Y-type molecular sieve catalyst, in particular to application in the synthesis of ethyl lactate from dihydroxyacetone. Background Art
[0002] In the synthesis of ethyl lactate, the traditional method relies on the esterification reaction of lactic acid and ethanol under catalyst conditions. However, the large-scale production of lactic acid mainly relies on the batch fermentation process of glucose under anaerobic conditions. This fermentation process usually takes 2 to 4 days and requires the continuous addition of calcium hydroxide to maintain a neutral pH value so that the bacteria can function optimally, thereby forming calcium lactate. After the calcium lactate crystallizes, it is acidified with sulfuric acid to release crude lactic acid and gypsum. Typically, for every ton of lactic acid produced, one ton of gypsum is formed. Further purification of lactic acid is achieved by esterification to methyl lactate, followed by distillation and hydrolysis to obtain pure lactic acid. This process is complicated and the post-processing is cumbersome, resulting in a high production cost of pure lactic acid. Therefore, there is an urgent need to develop new chemical catalytic processes for the direct extraction of lactic acid from raw biomass and its derivatives.
[0003] As a versatile platform molecule, glycerol has an annual production of 21 million tons and is still growing rapidly. Glycerol can be converted into various value-added chemicals through dehydration, oxidation and hydrogenation reactions. Among them, dihydroxyacetone (DHA) or glyceraldehyde (GLY), the main oxidation products of glycerol, are important intermediates in organic synthesis. DHA can be catalytically converted into lactic acid or lactate in water or alcohol, which is a cost-effective alternative to traditional plant biomass fermentation and complex purification processes and shorten the production cycle.
[0004] In the production process of ethyl lactate, regulation The ratio of B acid (B acid) and Lewis acid (L acid) is crucial to improving the efficiency of the reaction. B acid helps dehydrate DHA to form methylglyoxal, while L acid promotes the reaction of methylglyoxal with ethanol to form ethyl lactate. Studies have shown that catalysts containing two acid sites show higher efficiency and selectivity in the conversion of DHA to ethyl lactate. For example, the yield of ethyl lactate can be significantly improved in catalysts containing B acid and L acid sites. In addition, by regulating the ratio of acid sites, the performance of the catalyst can be optimized and the formation of by-products can be reduced, thereby increasing the yield of ethyl lactate.
[0005] Molecular sieves have highly regular micropores and mesoporous structures. These channels provide a large number of active sites, which are conducive to the adsorption and diffusion of reactant molecules. Y-type molecular sieves, in particular, have a three-dimensional channel structure, which can effectively increase the contact probability of reactants and enhance catalytic efficiency. The acid sites (B acid and L acid) in the molecular sieve are crucial for the reaction of DHA to ethyl lactate. The B acid site helps the dehydration of DHA to form methylglyoxal, while the L acid site promotes the reaction of methylglyoxal with ethanol to form ethyl lactate. By regulating the ratio of acid sites in the molecular sieve, the performance of the catalyst can be optimized and the yield of ethyl lactate can be increased. The use of molecular sieve catalysts for the reaction of DHA to ethyl lactate can simplify the traditional complex fermentation and purification processes, reduce operating steps and production costs. At the same time, by optimizing the catalyst and reaction conditions, the generation of by-products can be reduced, environmental pollution can be reduced, and the requirements of green chemistry can be met.
[0006] By introducing heteroatoms such as titanium (Ti) into the molecular sieve, the acid sites and electronic structure of the molecular sieve can be significantly regulated. Ti atoms, as Lewis acid centers, can enhance the L acid sites of the molecular sieve while stabilizing the activity of the B acid sites, thereby improving the overall activity and selectivity of the catalyst. Its main mechanisms include the following aspects: (1) Structural modification: After Ti atoms enter the Y-type molecular sieve framework, they will change the local structure and electronic distribution of the molecular sieve. Specifically, the introduction of Ti-O bonds replaces part of the Al-O-Si bonds, resulting in a redistribution of the acid sites in the molecular sieve structure. The introduction of Ti not only introduces new acid sites, but may also trigger the rearrangement of existing acid sites, resulting in the simultaneous existence of Acid and Lewis acid sites. This structural modification enhances the catalytic performance of the molecular sieve. (2) Formation of acid centers: In the Ti-doped Y-type molecular sieve framework, Ti 4+ As a Lewis acid center, the O 2- As Acid center. 4+ It has strong electron attraction ability and can form new Lewis acid centers, thereby increasing the proportion of Lewis acid in the molecular sieve. Acid sites are also affected by Ti doping, and their acid strength and quantity change. The formation of such acid centers is the key mechanism for Ti doping to regulate acid sites. (3) Interaction regulation: After Ti doping, Ti4+ interacts with the Si-OH-Al groups in the molecular sieve, resulting in The rebalancing of the ratio of Ti to Lewis acid. 4+ Can enhance the acidity of the surrounding oxygen atoms, making some The acid sites are converted into Lewis acid sites, thereby achieving the regulation of the ratio of B acid to L acid. This interaction regulation mechanism further optimizes the catalytic performance of the molecular sieve and improves its efficiency in the conversion of dihydroxyacetone (DHA) to ethyl lactate.
[0007] In summary, molecular sieves, especially Ti-doped Y-type molecular sieves, have become ideal catalysts for the synthesis of ethyl lactate from dihydroxyacetone due to their unique pore structure, adjustable acid sites, enhanced effect of heteroatom doping, excellent thermal stability and hydrothermal stability, simplified process and green environmental protection. These characteristics significantly improve the catalytic efficiency and yield, and promote the application of this reaction in industrial production.
[0008] The preparation methods of Ti-doped ultra-stable Y-type molecular sieves mainly include hydrothermal synthesis, sol-gel, template and post-treatment modification. (1) Hydrothermal synthesis: This method realizes Ti doping under relatively mild conditions, is easy to operate, and the generated molecular sieve has high crystallinity and stability, which is suitable for a variety of catalytic reactions. However, the reaction time is long and requires autoclave equipment. (2) Sol-gel method: This method can accurately control the doping amount of Ti and distribute it evenly. The preparation process is flexible and has strong controllability. It is suitable for a variety of precursors. However, gel cracking is prone to occur during the preparation process, which affects the mechanical strength of the final material and the subsequent processing steps are complicated. (3) Template method: This method can generate molecular sieves with regular mesoporous structures, significantly improve the diffusion rate of macromolecular reactants, and is suitable for a variety of catalytic reactions. However, the cost of using template agents is high, the removal process of template agents is complicated, and it is easy to cause pollution. (4) Post-treatment modification: This method can be modified on the basis of existing molecular sieves. By adjusting the treatment time and reaction conditions, efficient Ti doping can be achieved, and the process is flexible. However, the modification process may cause partial collapse of the molecular sieve structure, affecting the catalytic performance, and the post-treatment conditions need to be strictly controlled.
[0009] Ti-doped ultra-stable Y-type zeolite catalysts reduce by-product generation and environmental pollution through their efficient catalytic performance and environmental protection characteristics, meeting the requirements of green chemistry. Future development will pay more attention to environmental protection and sustainability to meet the needs of industrial production for green processes. Future research will focus on the following aspects: (1) Multifunctional catalyst development: By precisely controlling the Ti doping amount and distribution, the acid site ratio of the catalyst is optimized to adapt to different reaction conditions and requirements. (2) Nanotechnology application: By controlling the structure and composition at the nanoscale, the activity and stability of the catalyst are further improved. (3) High-throughput screening technology and big data analysis: Rapidly optimize catalyst formulations and reaction conditions to improve R&D efficiency and success rate. (4) Industrial application: Promote the transformation of new catalyst technologies in the laboratory to industrial applications, solve problems such as large-scale production of catalysts, reaction equipment optimization and process flow improvement, thereby improving overall production efficiency and reducing costs.
[0010] By meeting these technical requirements, Ti-doped ultra-stable Y-type zeolite catalyst will play a greater role in the reaction of dihydroxyacetone to synthesize ethyl lactate, promoting its widespread application in industrial production. Summary of the invention
[0011] The purpose of the present invention is to provide a preparation method and application of a Ti-doped ultra-stable Y-type molecular sieve catalyst, by precisely controlling the Ti doping amount and distribution, optimizing the acid site ratio of the catalyst to adapt to different reaction conditions and requirements, solving problems such as large-scale production of catalysts, reaction equipment optimization and process flow improvement, thereby improving overall production efficiency and reducing costs.
[0012] The technical solution of the present invention is:
[0013] A preparation method of a Ti-doped ultrastable Y-type molecular sieve catalyst comprises the following steps: the silicon-aluminum atomic ratio of the original ultrastable Y-type molecular sieve is 2-100, the ultrastable Y-type molecular sieve contains non-framework aluminum, and the content of the non-framework aluminum is not less than 10% by mass percentage of the non-framework aluminum to the total aluminum content; in an esterification reaction system of lactic acid and ethanol, the ultrastable Y-type molecular sieve containing the non-framework aluminum is treated, the molar ratio of lactic acid to ethanol is 1:1-1:5, and a titanium source is added to the reaction system to synthesize the Ti-doped ultrastable Y-type molecular sieve in one step, the amount of the titanium source added is 0.1-10 by mass ratio of titanium atoms to the ultrastable Y-type molecular sieve, the treatment temperature is 60-80°C, and the treatment time is 6-15 hours; in the initial reaction stage, a low pH environment promotes the dealumination of the ultrastable Y-type molecular sieve containing the non-framework aluminum; as the reaction proceeds, the lactic acid is gradually consumed, creating a mild pH environment, and promoting the insertion of titanium into the silanol nest formed by the dealumination of the molecular sieve.
[0014] The preparation method of the Ti-doped ultrastable Y-type molecular sieve catalyst is preferably such that the silicon-aluminum atomic ratio of the original ultrastable Y-type molecular sieve is 4-20, and the content of non-framework aluminum in the ultrastable Y-type molecular sieve is 15-50% by mass percentage of non-framework aluminum to total aluminum content.
[0015] In the method for preparing the Ti-doped ultrastable Y-type molecular sieve catalyst, preferably, the molar ratio of lactic acid to ethanol is 1:2 to 1:4.
[0016] The method for preparing the Ti-doped ultra-stable Y-type molecular sieve catalyst uses titanium sources including titanium tetrachloride, isopropyl titanate, tetrabutyl titanate, isooctyl titanate or tetraethyl titanate.
[0017] In the method for preparing the Ti-doped ultrastable Y-type molecular sieve catalyst, preferably, the amount of titanium source added is 0.1 to 1 in terms of the mass ratio of titanium atoms to the ultrastable Y-type molecular sieve.
[0018] In the preparation method of the Ti-doped ultrastable Y-type molecular sieve catalyst, the pH value of the low pH environment is 0.5-1.5, and the pH value of the mild pH environment is 1.5-2.0.
[0019] The Ti-doped ultra-stable Y-type molecular sieve catalyst preparation method is described. The Ti-doped ultra-stable Y-type molecular sieve prepared by the method has high crystallinity and high micropore volume and mesopore volume, with a relative crystallinity greater than 90% and a micropore volume greater than 0.3 cm 3 / g, mesopore volume greater than 0.2cm 3 / g; Ti exists in the molecular sieve framework in the form of tetracoordinated Ti, so that the molecular sieve has a suitable ratio of L acid to B acid, and the L acid amount / B acid amount is greater than 1.
[0020] The method for preparing the Ti-doped ultrastable Y-type molecular sieve catalyst uses Fe, Sn or Zr doping instead of Ti doping, and is also suitable for preparing Fe, Sn or Zr doped ultrastable Y-type molecular sieve.
[0021] The invention discloses an application of a Ti-doped ultra-stable Y-type molecular sieve catalyst. The Ti-doped ultra-stable Y-type molecular sieve catalyst has a suitable ratio of Br(Ⅱ) acid to L(Ⅱ) acid. The Br(Ⅱ) acid is helpful for the dehydration reaction of dihydroxyacetone (DHA), and the L(Ⅱ) acid promotes the generation of ethyl lactate from methylglyoxal and ethanol. The catalyst is applied in the reaction process of preparing ethyl lactate from dihydroxyacetone, and the catalytic activity and ethyl lactate selectivity are higher than those of commercial TS-1 titanium silicon molecular sieve, Ti-Beta molecular sieve, Sn-Beta molecular sieve and Sn-SBA-15 molecular sieve.
[0022] The application of the Ti-doped ultra-stable Y-type molecular sieve catalyst has good crystallinity and recycling performance, and the catalyst recovery rate is greater than 98%.
[0023] The design concept of the present invention is:
[0024] Tetrabutyl titanate is added to the reaction system in which ultra-stable Y-type molecular sieve containing non-framework titanium catalyzes the esterification reaction of lactic acid and ethanol to produce ethyl lactate, and titanium-doped ultra-stable Y-type molecular sieve is prepared through the dealumination and titanium insertion reaction process in the ultra-stable Y-type molecular sieve. The reaction mechanism of the Ti-doped ultra-stable Y-type molecular sieve is as follows:
[0025] 1) Dealumination: During the esterification reaction of lactic acid and ethanol, the ultra-stable Y-type molecular sieve containing non-framework aluminum undergoes dealumination transformation to form a molecular sieve containing silanol nests. These silanol nests provide space and reaction sites for the subsequent insertion of Ti ions. Dealumination not only increases the number of silanol nests, but also reduces the negative impact of aluminum ions in the molecular sieve framework, thereby optimizing the catalytic performance.
[0026] 2) Titanization: The Ti ions introduced into the reaction system mainly react with silanol nests to form Si-O-Ti bonds, thereby entering the molecular sieve framework. 4+ As a Lewis acid center, it forms coordination bonds with oxygen atoms in the silanol nest, thereby stabilizing the molecular sieve structure and increasing the number of Lewis acid sites. Ti insertion not only changes the acidity distribution of the molecular sieve, but also introduces new active sites, thereby enhancing the catalytic performance.
[0027] 3) Formation of dual active sites: Through dealumination and titanation treatment, dual active sites with framework-substituted Ti species and tri-coordinated aluminum species are formed. The Ti species in the framework acts as a Lewis acid center, while the tri-coordinated aluminum species also has Lewis acidity. The synergistic effect of this dual active site significantly improves the catalytic performance of the catalyst.
[0028] 4) Relationship between structure and performance: Studies have shown that Ti-doped ultra-stable Y-type zeolites exhibit excellent catalytic performance in selective oxidation reactions such as oxidative desulfurization and Baeyer-Villiger oxidation. By controlling the reaction time, the amount of TBOT added during the titanation process, and the ratio of lactic acid to ethanol, the number and distribution of Lewis acid sites of the Ti-doped zeolite can be optimized, thereby improving the catalytic performance. Ti-doped zeolites exhibit higher Lewis acid site strength and number, which is of great significance for improving catalytic efficiency and selectivity.
[0029] The present invention has the following advantages and beneficial effects:
[0030] 1. Innovation in doping methods: By introducing tetrabutyl titanate during the post-esterification treatment of ultra-stable Y-type molecular sieves containing non-framework aluminum, a titanium-doped ultra-stable Y-type molecular sieve catalyst with a suitable ratio of B acid and L acid was successfully prepared. The introduction of titanium can reduce the defect sites generated by dealumination, maintain the stability of the molecular sieve framework, and exist in an isolated tetrahedral coordination state, thereby improving the activity and stability of the catalyst.
[0031] 2. Acid site regulation: By precisely regulating the ratio of B acid and L acid in the catalyst, the process of DHA dehydration to form methylglyoxal and its reaction with ethanol to form ethyl lactate was optimized. This regulation not only improved the catalytic efficiency, but also reduced the formation of by-products, so that the yield of ethyl lactate reached 81.3% under the optimal conditions, demonstrating the high efficiency and feasibility of the catalyst in industrial applications.
[0032] 3. Improve the crystallinity and stability of molecular sieve catalysts during the reaction process: The obtained catalyst has good crystallinity and recycling performance, and the catalyst recovery rate is greater than 98%. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] FIG1 is an XRD pattern (a) of adding tetrabutyl titanate (Ti-USY-3-yh) at different times (y=3, 6, 9, 12, 15) during the post-treatment of ultra-stable Y-type molecular sieve with non-framework aluminum by lactic acid and ethanol solution, and an XRD pattern (b) of the sample (USY5-3-12h) of the ultra-stable Y-type molecular sieve with non-framework aluminum by post-treatment of lactic acid and ethanol solution 12 hours later. It can be seen from FIG1 (a) and FIG1 (b) that the USY5 molecular sieve has typical diffraction peaks at 6.0°, 10.0°, 11.8°, 15.6°, 20.8° and 23.6°, and the USY5-3-12h sample without titanium source shows weaker diffraction peaks, indicating the collapse of the framework structure and the formation of amorphous silicon aluminum oxide. After adding the titanium source, the molecular sieve maintains the diffraction peak. As time goes by, the lattice expands and the diffraction peak of the (111) crystal plane of the TiUSY-3-yh sample shifts to a lower angle. This is mainly due to the Ti 4+ Inserted into the framework. The addition of titanium source is beneficial to maintain the stability of the framework during the dealumination process. XRD spectrum comparison and relative crystallinity analysis (46.0% increased to 60.6%) show that Ti 4+ Insertion reduces dealumination defect sites and improves framework stability.
[0034] Figure 2 shows the solid-state NMR images of (a) USY5, (b) USY5-3-12h and (c) TiUSY-3-12h samples. 29 Si spectrum. Figure 2(a)-Figure 2(c)It can be seen that a large number of Si(OH) groups and amorphous silica appeared in the USY5-3-12h sample without titanium source, indicating that the framework aluminum was removed and the framework collapsed. After adding titanium source, a large number of Si(1M) (M=Al, Ti) groups existed in the TiUSY-3-12h sample, indicating that Ti was inserted into the molecular sieve framework, replacing the position of Al, avoiding the collapse of the framework caused by the rapid removal of Al, thereby stabilizing the molecular sieve framework structure.
[0035] Figure 3 shows the (a) UV-Vis, (b) FT-IR and (c) Ti2p XPS spectra of USY5, USY5-3-12h and TiUSY-3-yh samples. As can be seen from Figure 3(a), the TiUSY molecular sieve shows a sharp and strong tetracoordinate titanium absorption peak at 220nm, and the 250-290nm region shows a broad shoulder signal of the mononuclear octahedral titanium species. There is no signal above 320nm, indicating that there is no rutile form of titanium oxide. As can be seen from Figure 3(b), during the 0-9h doping process, the sample vibration peak gradually blue-shifted, indicating that in this process, the effect of dealumination on the skeleton vibration peak is much greater than that of Ti inserted into the skeleton. In 9-15h, it is clearly found that the sample vibration peak is red-shifted, indicating that in this process, the effect of Ti inserted into the molecular sieve skeleton on the skeleton vibration peak is greater than that of the molecular sieve dealumination. As can be seen from Figure 3(c), Ti 4+ It mainly exists in the Y molecular sieve framework in an isolated tetrahedral coordination state, and the characteristic peak intensity first increases and then decreases with the extension of titanation time, reaching the maximum at 12 hours.
[0036] Figure 4 The HAADF-STEM image of TiUSY-3-12h sample (a) and the corresponding EDX line scanning element analysis (b). Figure 4 (a) and Figure 4 As can be seen from (b), the titanium-doped ultrastable Y-type zeolite has a connected pore structure and uniformly distributed Si, Al, O, and Ti elements, indicating that the TiUSY zeolite prepared by the one-step method achieves uniform distribution of elements.
[0037] Figure 5 The XRD patterns of TiUSY-x-12h samples at different acid-alcohol ratios (molar ratios) are shown in Figure 1. The horizontal axis 2θ is the diffraction angle (°), and the vertical axis Intensity is the relative intensity (au). Figure 5 It can be seen that after treating USY5 molecular sieve with solution systems of different acid-alcohol ratios for 12 hours, the obtained TiUSY-x-12h sample showed characteristic peaks of Y-type molecular sieve at around 6.0°, 10.0°, 11.8°, 15.6°, 23.6° and 27.4°, indicating that the sample maintained a good framework structure. Figure 5It shows that with the increase of acid-alcohol ratio, the diffraction peak of TiUSY-x-12h sample on the (111) crystal plane shifts to a high angle, indicating that the lattice shrinks. The decrease in relative crystallinity also indicates that the framework is damaged, mainly due to the removal of a large amount of framework aluminum. When the acid-alcohol ratio is 1.0, Si / Ti is 27.1 and Si / Al is 20.5; when the acid-alcohol ratio is increased to 1.5 and above, Si / Ti basically remains at around 25, and Si / Al increases from 24.6 to 35.5. It can be seen that the increase in the acid-alcohol ratio has little effect on titanization, but significantly affects dealumination.
[0038] Figure 6 shows the UV-Vis spectrum (a), FT-IR spectrum (b) and Ti2p XPS spectrum (c). In Figure 6(a), the horizontal axis Wavelength is the wavelength (nm), and the vertical axis Absorbance is the absorbance (au); in Figure 6(b), the horizontal axis Wavelength is the wavelength (nm), and the vertical axis Transmittance is the transmittance (au); in Figure 6(c), the horizontal axis Wavelength is the wavelength (nm), and the vertical axis Transmittance is the transmittance (au). It can be seen from the UV-Vis spectrum of Figure 6(a) that the TiUSY-x-yh sample shows an absorption peak of tetracoordinated titanium at 220nm, and a broad shoulder signal of a mononuclear octahedral titanium species is shown in the 250-290nm region. There is no signal above 320nm, indicating that there is no anatase form of titanium oxide. It can be seen from the FT-IR spectrum of Figure 6(b) that the sample has an absorption peak at 790cm -1 and 920~1220cm -1 The Si-O-Al stretching vibration peak is shown at 969 cm-1. -1 Si-O-Ti stretching vibration peak appears at . As the titanation time increases, the skeleton vibration peak blue shifts, indicating that the effect of dealumination is greater than that of Ti insertion. From the XPS spectrum of Figure 6(c), it can be seen that the sample shows characteristic peaks of isolated Ti ions at 460.2eV and 465.5eV, and there is no polymerized TiO2 signal at 458.0eV. The intensity of the characteristic peak increases when the acid-alcohol ratio increases from 1.0 to 3, and decreases slightly when it decreases from 1.5 to 4.0, indicating that the degree of titanation is the highest when the acid-alcohol ratio is 3. DETAILED DESCRIPTION
[0039] In the specific implementation process, the present invention proposes a preparation method of a Ti-doped ultra-stable Y-type molecular sieve catalyst, comprising the following steps: in the esterification reaction system of lactic acid and ethanol, treating the ultra-stable Y-type molecular sieve containing non-framework aluminum, and adding a titanium source to the above reaction system to synthesize the Ti-doped ultra-stable Y-type molecular sieve in one step. The mechanism of the preparation method is as follows: in the initial reaction stage, the low pH environment promotes the dealumination of the ultra-stable Y-type molecular sieve containing non-framework aluminum; as the reaction proceeds, the lactic acid is gradually consumed, creating a mild pH environment, which promotes the insertion of titanium into the silanol nests formed by the dealumination of the molecular sieve. The Ti-doped ultra-stable Y-type molecular sieve prepared by this method has high crystallinity, and compared with the original ultra-stable Y, the relative crystallinity is greater than 90%; it has a higher micropore volume and mesopore volume, and the micropore volume is greater than 0.3cm 3 / g, mesopore volume greater than 0.2cm 3 / g; Ti exists in the molecular sieve framework in the form of tetracoordinated Ti, so that the molecular sieve has a suitable ratio of L acid to B acid, and the L acid amount / B acid amount is greater than 1.
[0040] Below, the present invention is further described in detail by examples and comparative examples.
[0041] Example 1
[0042] This example introduces the effect of reaction time on the physical and chemical properties and catalytic performance of the product during the preparation of Ti atom-doped ultrastable Y-type molecular sieve. The specific steps are as follows: Take 1.5g of ultrastable Y-type molecular sieve (silicon-aluminum atomic ratio of 5, containing 20wt% non-framework aluminum, referred to as: USY5), add 0.1mol ethanol and 0.3mol lactic acid mixed solution, and stir evenly. Slowly add 3mmol tetrabutyl titanate to the above mixture. The mixture is placed in a 65℃ oil bath for treatment, and the treatment time is 6 hours, 9 hours, 12 hours and 15 hours respectively. After treatment, the mixture is centrifuged and washed and dried in a 100℃ oven for 12 hours. After drying, the sample is placed in a muffle furnace at 550℃ and roasted for 2 hours to obtain a titanium atom-doped USY5 sample, recorded as TiUSY-3-xh (3 represents the acid-alcohol ratio, x is the reaction time, which is 6 hours, 9 hours, 12 hours and 15 hours respectively).
[0043] The preparation method of the comparative sample is the same, except that tetrabutyl titanate is not added, the reaction time is 12 hours, and the obtained sample is USY5-3-12h.
[0044] The catalytic performance evaluation experiment is as follows: taking the isomerization reaction of dihydroxyacetone (DHA) and ethanol to prepare ethyl lactate as a reaction model, 1 mmol of dihydroxyacetone, 4 mL of ethanol and 75 mg of catalyst were added in sequence into a 25 mL pressure-resistant reaction bottle, with a stirring speed of 500 rpm, a reaction temperature of 90°C and a reaction time of 5 hours.
[0045] Experimental results and analysis:
[0046] Figure 1 is an XRD spectrum: As shown in Figures 1(a) and 1(b), the USY5 molecular sieve shows typical Y-type molecular sieve diffraction peaks near 6.0°, 10.0°, 11.8°, 15.6°, 20.8° and 23.6°. In the USY5-3-12h sample prepared without adding a titanium source, the diffraction peak is weak, indicating that the skeleton structure collapses, and the amorphous silicon aluminum oxide leads to the generation of a broad peak, indicating that the formation of the amorphous phase is accompanied by the destruction of the skeleton structure. In contrast, the molecular sieve with the addition of a titanium source can still maintain the diffraction peak of the USY5 molecular sieve. As the treatment time increases, the lattice expands, and the diffraction peak of the TiUSY-3-yh sample on the (111) crystal plane shifts to a low angle; because under acidic conditions, lactic acid will remove the skeleton aluminum, resulting in lattice contraction, causing the XRD diffraction peak to move toward a high angle, and the final diffraction peak of the (111) crystal plane shifts to a low angle, which is the result of dealumination and Ti 4+ The result of the two processes of inserting the skeleton, in which Ti 4+ The main effect of the framework insertion process on the framework deformation is that Ti is inserted into the framework of the molecular sieve, and the addition of the titanium source is beneficial to the stability of the framework of the molecular sieve during the dealumination process.
[0047] Figure 2 29 Si solid NMR spectrum: Figure 2(a)-Figure 2(c) As shown in the figure, a large number of Si(OH) groups and amorphous silica appeared in the USY5-3-12h sample without titanium source, indicating that the framework aluminum was removed and the framework collapsed. After adding titanium source, a large number of Si(1M) (M=Al, Ti) groups were present in the TiUSY-3-12h sample, indicating that Ti was inserted into the molecular sieve framework, replacing the position of Al, avoiding the framework collapse caused by the rapid removal of Al and stabilizing the framework structure.
[0048] Figure 3 shows the UV-Vis (a), FT-IR (b) and Ti 2p XPS (c) spectra: The UV-Vis spectrum shows that the TiUSY-3-12h sample shows a sharp and strong tetracoordinate titanium absorption peak at 220nm, and the 250-290nm region shows a broad shoulder signal of a mononuclear octahedral titanium species, and there is no signal above 320nm, indicating that there is no rutile form of titanium oxide. The FT-IR spectrum shows that during the 0-9h doping process, the sample vibration peak gradually blue-shifted, indicating that the effect of dealumination on the skeleton vibration peak is greater than that of Ti insertion into the skeleton. In the 9-15h range, the vibration peak red-shifted, indicating that the effect of Ti insertion on the skeleton vibration peak is greater than that of dealumination. The Ti2pXPS spectrum shows that Ti 4+It mainly exists in the Y molecular sieve framework in an isolated tetrahedral coordination state. With the extension of titanation time, the characteristic peak intensity first increases and then decreases, reaching the maximum after 12 hours.
[0049] Figure 4 For HAADF-STEM and EDX line scanning element analysis: Figure 4 (a) and Figure 4 As shown in (b), the Ti-doped ultrastable Y-type zeolite has a connected pore structure and uniformly distributed Si, Al, O, and Ti elements, indicating that the sample prepared by this method achieves uniform distribution of elements.
[0050] Table 1 shows the relative crystallinity of the samples: As shown in Table 1, the relative crystallinity of the original USY5 molecular sieve is 100%. During the treatment process, the relative crystallinity decreases significantly due to the increase in framework defects caused by dealumination. After 9 to 15 hours of post-treatment, the relative crystallinity of TiUSY-3-yh increases (from 69% to 90.9%), which may be due to the Ti 4+ The skeleton is continuously inserted to reduce the defect sites caused by dealumination and keep the skeleton relatively stable.
[0051] Table 2 shows the physical adsorption results: As shown in Table 2, relative to the USY5-3-12h sample, the sample obtained by adding tetrabutyl titanate during the post-treatment process has a higher micropore volume and mesopore volume.
[0052] Table 3 shows the NH3-TPD and Py-FTIR data: As shown in Table 3, after 6 hours of titanation, the L-acid of USY5 was greatly reduced, indicating that most of the L-acid was removed by lactic acid. The intensity of the acidic peak gradually decreased, while the Lewis acidic peak gradually increased, reaching a maximum value after 12 hours and then decreasing. From 1 to 12 hours, the molecular sieve dealumination produced a large number of silanol vacancies, and Ti reacted with the silanol vacancies and inserted into the framework, resulting in a decrease in the amount of B acid and an increase in the amount of L acid; the amount of L acid decreased after continuing the titanization for 15 hours.
[0053] Table 4 shows the results of DHA synthesis of ethyl lactate: As shown in Table 4, USY5 and USY5-3-12h have no catalytic activity for DHA synthesis of ethyl lactate, while TiUSY-3-xh shows good activity, indicating that Ti inserted into the framework improves the catalytic performance. As the titaniumization time increases, the yield of ethyl lactate shows a "volcano-type" trend, and the yield of the 12-hour TiUSY-3-12h sample is the highest (81.3%). Controlling the esterification reaction time can regulate the dealumination and Ti insertion amount of the molecular sieve, adjust the ratio of B acid and L acid, and achieve synergistic catalysis.
[0054] Example 2
[0055] In this embodiment, the influence of different acid-alcohol ratios on the physicochemical properties of Ti-doped mesoporous Y molecular sieves is mainly introduced. The specific steps are as follows: Take 1.5g of ultra-stable Y-type molecular sieve (USY5), the silicon-aluminum atomic ratio is about 5, add 0.1mol of ethanol and lactic acid mixed solution, the ratio of lactic acid to ethanol is 1.0, 1.5, 3.0 and 4.0 respectively, and stir evenly. Slowly add 3mmol of tetrabutyl titanate to the above mixture. The mixture is placed in a 65°C oil bath for 12 hours. After treatment, the mixture is centrifuged and washed and dried in a 100°C oven for 12 hours. After drying, the sample is placed in a muffle furnace at 550°C and calcined for 2 hours to obtain a heteroatom-modified USY5 sample, recorded as TiUSY-y-12h (y represents the acid-alcohol ratio, which is 1.0, 1.5, 3.0 and 4.0 respectively).
[0056] The experimental process for evaluating the catalytic performance is as follows: taking the isomerization reaction of dihydroxyacetone (DHA) and ethanol to prepare ethyl lactate as a reaction model, 1 mmol DHA, 4 mL ethanol and 75 mg catalyst were added in sequence into a 25 mL pressure-resistant reaction bottle, with a stirring speed of 500 rpm, a reaction temperature of 90°C and a reaction time of 5 hours.
[0057] Figure 5 For XRD spectrum: Figure 5 As shown, after treating USY5 molecular sieve with solution systems of different acid-alcohol ratios for 12 hours, the obtained TiUSY-x-12h sample showed characteristic peaks of Y-type molecular sieve at around 6.0°, 10.0°, 11.8°, 15.6°, 23.6° and 27.4°, indicating that the sample maintained a good framework structure. Figure 5 It shows that with the increase of acid-alcohol ratio, the diffraction peak of TiUSY-x-12h sample on the (111) crystal plane shifts to a high angle, indicating that the lattice shrinks. The decrease in relative crystallinity also indicates that the framework is damaged, mainly due to the removal of a large amount of framework aluminum. When the acid-alcohol ratio is 1.0, Si / Ti is 27.1 and Si / Al is 20.5; when the acid-alcohol ratio is increased to 1.5 and above, Si / Ti basically remains at around 25, and Si / Al increases from 24.6 to 35.5. It can be seen that the increase of acid-alcohol ratio can increase the amount of Ti insertion and the amount of aluminum removal.
[0058] Figure 6 shows the UV-Vis (a), FT-IR (b) and Ti2p XPS (c) spectra: From the UV-Vis spectrum, it can be seen that the TiUSY-x-yh sample shows an absorption peak of tetracoordinated titanium at 220nm, and the 250-290nm region shows a broad shoulder signal of mononuclear octahedral titanium species, and there is no signal above 320nm, indicating that there is no anatase-formed titanium oxide. From the FT-IR spectrum, it can be seen that the sample has an absorption peak of tetracoordinated titanium at 790cm -1 and 920~1220cm -1The Si-O-Al stretching vibration peak is shown at 969 cm -1 Si-O-Ti stretching vibration peak appears at . As the titanation time increases, the skeleton vibration peak blue shifts, indicating that the effect of dealumination is greater than that of Ti insertion. From the XPS spectrum, it can be seen that the sample shows characteristic peaks of isolated Ti ions at 460.2eV and 465.5eV, and there is no polymerized TiO2 signal at 458.0eV. The intensity of the characteristic peak increases when the acid-alcohol ratio increases from 1.0 to 3, and decreases slightly when it decreases from 1.5 to 4.0, indicating that the degree of titanation is the highest when the acid-alcohol ratio is 3.
[0059] As shown in Table 5, after the USY5 molecular sieve was treated with a solution system with different acid-alcohol ratios for 12 hours, the relative crystallinity, silicon-aluminum ratio, and silicon-titanium ratio were obtained. It can be seen from the table that when the acid-alcohol ratio of the treatment solution system is 1.0, Si / Ti is 27.1 and Si / Al is 20.5. When the acid-alcohol ratio is increased to 1.5 or above, Si / Ti is basically maintained at around 25, and Si / Al is increased from 24.6 to 35.5.
[0060] As shown in Table 6, from the NH3-TPD and Py-FTIR data, it can be found that the amount of B acid gradually decreases, the amount of L acid gradually increases, and L / B gradually increases. When the acid-alcohol ratio continues to increase, the amount of B acid and L acid decreases. Therefore, it is concluded that when the acid-alcohol ratio is 3, the TiUSY molecular sieve has a higher amount of L acid and a higher ratio of L acid to B acid.
[0061] As shown in Table 7, it can be seen from the physical adsorption data that with the increase of the acid-alcohol ratio, the specific surface area and micropore volume of the TiUSY-x-12h sample increase. The micropore and mesopore volumes of TiUSY-3-12h are 0.32 cm3·g -1 and 0.24 cm3·g -1 .
[0062] As shown in Table 8, the results of the reaction of the prepared sample catalyzing dihydroxyacetone to synthesize ethyl lactate. It can be seen that as the acid-alcohol ratio increases from 1.5 to 3, the initial conversion rate of DHA decreases from 47.0% to 38.6%. This phenomenon is mainly due to the increase in the acid-alcohol ratio, which leads to an increase in the degree of dealumination of the USY5 molecular sieve (Si / Al increases from 20.5 to 30.2) and a decrease in the amount of B acid, thereby reducing the conversion rate of DHA. However, the yield of ethyl lactate gradually increases with the increase of the acid-alcohol ratio. When the acid-alcohol ratio is 3, the yield of ethyl lactate is the highest. After 1 hour of reaction, the yield of ethyl lactate of the sample was 38.4%; after 5 hours of reaction, the yield of ethyl lactate reached 81.3%
[0063] Example 3
[0064] This example introduces the effect of the type of titanium source on the catalytic performance of the product during the preparation of Ti atom-doped ultrastable Y-type molecular sieve. The specific steps are as follows:
[0065] Take 1.5g of ultra-stable Y-type molecular sieve (silicon-aluminum atomic ratio of 5, containing 20wt% non-framework aluminum, referred to as: USY5), add it to a mixed solution of 0.1mol ethanol and 0.3mol lactic acid, and stir evenly. Slowly add 3mmol tetraethyl titanate to the above mixture. The mixture is placed in a 65°C oil bath for 12 hours. After treatment, the mixture is centrifuged and washed and dried in an oven at 100°C for 12 hours. After drying, the sample is placed in a muffle furnace at 550°C and calcined for 2 hours to obtain a titanium atom-doped USY5 sample, recorded as TiUSY-3-12h-tetraethyl titanate. Take the same amount of USY molecular sieve, use titanium tetrachloride instead of tetraethyl titanate to perform the same treatment steps, recorded as TiUSY-3-12h-titanium tetrachloride. Use isooctyl titanate instead of tetraethyl titanate for treatment, recorded as TiUSY-3-12h-isooctyl titanate. Isopropyl titanate was used instead of tetraethyl titanate for treatment, and was recorded as TiUSY-3-12h-isopropyl titanate.
[0066] The experimental process for evaluating the catalytic performance is as follows: taking the isomerization reaction of dihydroxyacetone (DHA) and ethanol to prepare ethyl lactate as a reaction model, 1 mmol DHA, 4 mL ethanol and 75 mg catalyst were added in sequence into a 25 mL pressure-resistant reaction bottle, with a stirring speed of 500 rpm, a reaction temperature of 90°C and a reaction time of 5 hours.
[0067] As shown in Table 9, the samples prepared from titanium tetrachloride, isopropyl titanate, isooctyl titanate and tetraethyl titanate all showed excellent catalytic activity, which was comparable to the performance of the sample prepared from tetrabutyl titanate, demonstrating the universality of this method under different titanium source conditions.
[0068] Comparative Example 1
[0069] In this comparative example, the catalyst prepared in the present invention is compared with the commercial catalytic performance, and the comparative catalysts used include TS-1 titanium silicon molecular sieve, Ti-Beta molecular sieve, Sn-Beta molecular sieve, and Sn-SBA-15 molecular sieve.
[0070] The experimental process for evaluating the catalytic performance is as follows: taking the isomerization reaction of dihydroxyacetone (DHA) and ethanol to prepare ethyl lactate as a reaction model, 1 mmol DHA, 4 mL ethanol and 75 mg catalyst were added in sequence into a 25 mL pressure-resistant reaction bottle, with a stirring speed of 500 rpm, a reaction temperature of 90°C and a reaction time of 5 hours.
[0071] As shown in Table 10, compared with commercial TS-1 titanium silicon molecular sieve and Ti-Beta molecular sieve, Sn-Beta molecular sieve and Sn-SBA-15 molecular sieve reported in the literature, the catalyst prepared by the present invention exhibits more excellent catalytic activity. As shown in Table 11, compared with commercial TS-1 titanium silicon molecular sieve and Ti-Beta molecular sieve, Sn-Beta molecular sieve and Sn-SBA-15 molecular sieve reported in the literature, the catalyst prepared by the present invention still maintains the same reaction activity as the fresh catalyst during the 5th cycle of use, and the catalyst recovery rate is higher than 98%, while the recovery rate of the comparative catalyst is lower than 80%. As shown in Tables 12 and 13, the physical adsorption and acid site results of the catalyst before the reaction and after 5 cycles of use show that the pore structure and acid site structure of the catalyst remain stable, which is an important reason for its stable catalytic performance.
[0072] Table 1. Relative crystallinity of USY5, USY5-3-12h and TiUSY-3-yh samples
[0073] Catalyst Relative crystallinity(%) <![CDATA[Si / Al (atomic ratio) a > <![CDATA[Si / Ti (atomic ratio) a > USY5 100 5 / USY5-3-12h - 74 / TiUSY-3-6h 95.3 16.8 39.0 TiUSY-3-9h 69.0 20.6 31.8 TiUSY-3-12h 81.6 30.2 25.2 TiUSY-3-15h 90.9 32.7 25.1
[0074] In the table, a refers to ICP test, and Relative crystallinity refers to relative crystallinity.
[0075] Table 2. Physical adsorption results of USY5, USY5-3-12h and TiUSY-3-yh samples
[0076]
[0077]
[0078] In the table, Specific surface area is the specific surface area, S BET is the total specific surface area, S micro is the micropore specific surface area, S external is the external specific surface area, Specificpore volume is the pore volume, V micro is the micropore volume, V meso is the mesopore volume, V total is the total pore volume.
[0079] Table 3. NH3-TPD and Py-FTIR data analysis of USY5 and TiUSY-3-yh samples
[0080]
[0081] In the table, B: acidity (Brønsted acidity), L:Lewis acidity (Lewis acidity).
[0082] Table 4 Results of synthesis of ethyl lactate catalyzed by dihydroxyacetone of USY5, USY5-3-12h and TiUSY-3-yh samples
[0083] Sample USY5 USY5-3-12h TiUSY-3-6h TiUSY-3-9h TiUSY-3-12h TiUSY-3-15h <![CDATA[Final yield a ]]> <1 <1 38.3 65.6 81.3 70.3
[0084] In the table, a is the sample taken after 5 hours of reaction, and Final yield is the final conversion rate.
[0085] Table 5 Relative crystallinity of TiUSY-y-12h samples
[0086] Catalyst Relative crystallinity (%) Si / Al Si / Ti TiUSY-1-12h 60.3 20.5 27.1 TiUSY-1.5-12h 59.6 24.6 25.7 TiUSY-3-12h 54.4 30.2 25.2 TiUSY-4-12h 34.8 35.5 24.7
[0087] Table 6 NH3-TPD and Py-FTIR data analysis of TiUSY-y-12h sample
[0088]
[0089] Table 7 Physical adsorption results of TiUSY-y-12h samples
[0090]
[0091] Table 8 Catalytic results of TiUSY-y-12h samples
[0092] Sample <![CDATA[Initial DHA a (%)]]> <![CDATA[InitialEL a (%)]]> <![CDATA[Finalyield b (%)]]> TiUSY-1.0-12h 49.8 20.6 40.6 TiUSY-1.5-12h 47.0 31.6 55.0 TiUSY-3-12h 42.7 38.4 81.3 TiUSY-4.0-12h 38.6 34.8 75.2
[0093] In the table, a is the sample taken after 1 hour of reaction, b is the sample taken after 5 hours of reaction, Initial is the initial conversion rate, Finalyield is the final conversion rate, DHA is dihydroxyacetone, and EL is ethyl lactate.
[0094] Table 9 Catalytic results of samples prepared with different titanium sources
[0095] Sample <![CDATA[InitialDHA a (%)]]> <![CDATA[InitialEL a (%)]]> <![CDATA[Final yield b (%)]]> TiUSY-3-12h-Titanium tetrachloride 38.8 37.6 78.8 TiUSY-3-12h-Tetraethyl titanate 40.1 38.2 80.9 TiUSY-3-12h-Tetrapropyl titanate 40.2 38.1 80.3 TiUSY-3-12h-Tetrabutyl titanate 42.7 38.4 81.3 TiUSY-3-12h-Tetraoctyl titanate 39.7 37.9 79.6
[0096] In the table, a represents sampling after 1 h of reaction, and b represents sampling after 5 h of reaction.
[0097] Table 10 Comparison of catalytic performance of different catalysts
[0098] Sample <![CDATA[InitialDHA a (%)]]> <![CDATA[InitialEL a (%)]]> <![CDATA[Finalyield b (%)]]> TiUSY-3-12h 42.7 38.4 81.3 TS-1 Titanium Silica Molecular Sieve 21.2 32.5 66.7 Ti-Beta 25.6 31.5 67.7 Sn-Beta 24.6 29.8 63.2 Sn-SBA-15 27.2 31.5 70.2
[0099] In the table, a represents sampling after 1 h of reaction, and b represents sampling after 5 h of reaction.
[0100] Table 11 Comparison of catalytic performance of different catalysts after the fifth cycle
[0101]
[0102]
[0103] In the table, a represents sampling after 1 h of reaction, and b represents sampling after 5 h of reaction.
[0104] Table 12 Physical adsorption results of fresh and five-cycle TiUSY-3-12h samples
[0105]
[0106] Table 13 Acidic site characteristics of fresh and five-cycle TiUSY-3-12h samples
[0107]
[0108] These embodiments fully demonstrate the method for preparing Ti-doped ultra-stable Y-type molecular sieve by introducing a titanium source during the esterification reaction of an ultra-stable Y-type molecular sieve containing non-framework aluminum. Ti doping increases the ratio of L acid and B acid in the molecular sieve, so that it exhibits excellent performance in the reaction of preparing ethyl lactate from dihydroxyacetone, and provides a new way to regulate the acidic position of the molecular sieve. In the reaction of synthesizing ethyl lactate from dihydroxyacetone, the catalyst exhibits high activity and high selectivity for ethyl lactate, and has good recycling performance. This method not only simplifies the process flow and reduces production costs, but also provides an efficient and economical production process for ethyl lactate, which has significant industrial application prospects.
Claims
1. A method for preparing a Ti-doped ultrastable Y-type molecular sieve catalyst, characterized in that: The method comprises the following steps: the silicon-aluminum atomic ratio of the original ultra-stable Y-type molecular sieve is 2-100, the ultra-stable Y-type molecular sieve contains non-framework aluminum, the content of the non-framework aluminum is not less than 10% by mass percentage of the non-framework aluminum to the total aluminum content, the ultra-stable Y-type molecular sieve containing the non-framework aluminum is treated in an esterification reaction system of lactic acid and ethanol, the molar ratio of lactic acid to ethanol is 1:1-1:5, a titanium source is added to the reaction system, and the Ti-doped ultra-stable Y-type molecular sieve is synthesized in one step, the amount of the titanium source added is 0.1-10 by mass ratio of titanium atoms to the ultra-stable Y-type molecular sieve, the treatment temperature is 60-80°C, and the treatment time is 6-15 hours; in the initial reaction stage, a low pH environment promotes the dealumination of the ultra-stable Y-type molecular sieve containing the non-framework aluminum; as the reaction proceeds, the lactic acid is gradually consumed, creating a mild pH environment, and promoting the insertion of titanium into the silanol nest formed by the dealumination of the molecular sieve.
2. The method for preparing the Ti-doped ultrastable Y-type molecular sieve catalyst according to claim 1, characterized in that: Preferably, the silicon-aluminum atomic ratio of the original ultrastable Y-type molecular sieve is 4-20, and the content of non-framework aluminum in the ultrastable Y-type molecular sieve is 15-50% by mass percentage of non-framework aluminum to total aluminum content.
3. The method for preparing the Ti-doped ultrastable Y-type molecular sieve catalyst according to claim 1, characterized in that: Preferably, the molar ratio of lactic acid to ethanol is 1:2 to 1:
4.
4. The method for preparing the Ti-doped ultrastable Y-type molecular sieve catalyst according to claim 1, characterized in that: The titanium source used includes titanium tetrachloride, isopropyl titanate, tetrabutyl titanate, isooctyl titanate or tetraethyl titanate.
5. The method for preparing the Ti-doped ultrastable Y-type molecular sieve catalyst according to claim 1, characterized in that: Preferably, the amount of titanium source added is 0.1 to 1 in terms of the mass ratio of titanium atom to ultrastable Y-type molecular sieve.
6. The method for preparing the Ti-doped ultrastable Y-type molecular sieve catalyst according to claim 1, characterized in that: The pH value of a low pH environment is 0.5 to 1.5, and the pH value of a mild pH environment is 1.5 to 2.
0.
7. The method for preparing the Ti-doped ultrastable Y-type molecular sieve catalyst according to claim 1, characterized in that: The Ti-doped ultrastable Y-type molecular sieve prepared by the method has high crystallinity and high micropore volume and mesopore volume, with a relative crystallinity greater than 90% and a micropore volume greater than 0.3 cm 3 / g, mesopore volume greater than 0.2cm 3 / g; Ti exists in the molecular sieve framework in the form of tetracoordinated Ti, so that the molecular sieve has a suitable ratio of L acid to B acid, and the L acid amount / B acid amount is greater than 1.
8. The method for preparing the Ti-doped ultrastable Y-type molecular sieve catalyst according to claim 1, characterized in that: The method replaces Ti doping with Fe, Sn or Zr doping, and is also suitable for preparing Fe, Sn or Zr doped ultra-stable Y-type molecular sieves.
9. Use of the Ti-doped ultrastable Y-type molecular sieve catalyst according to any one of claims 1 to 8, characterized in that: The Ti-doped ultrastable Y-type molecular sieve catalyst has a suitable ratio of Br(Ⅱ) acid to L(Ⅱ) acid. Br(Ⅱ) acid contributes to the dehydration reaction of dihydroxyacetone (DHA), while L(Ⅱ) acid promotes the reaction of methylglyoxal and ethanol to produce ethyl lactate. The catalyst is used in the reaction process of preparing ethyl lactate from dihydroxyacetone, and its catalytic activity and selectivity for ethyl lactate are higher than those of commercial TS-1 titanium silicalite molecular sieve, Ti-Beta molecular sieve, Sn-Beta molecular sieve and Sn-SBA-15 molecular sieve.
10. The use of the Ti-doped ultrastable Y-type molecular sieve catalyst according to claim 9, characterized in that: The catalyst has good crystallinity and recycling performance, and the catalyst recovery rate is greater than 98%.